OP0259 The Interleukin 33/MIR29 Axis Regulates Differential Collagen Production in Tendinopathy. (23rd January 2014) - Millar, N. L.; Gilchrist, D. S.; Kurowska-Stolarska, M.; Murrell, G. A. C.; McInnes, I. B.
Abstract : Background: Tendon disorders comprise the commonest musculoskeletal clinical presentation and accordingly represent a significant unmet clinical need. Recent animal and human studies have highlighted a central role for inflammation and subsequent matrix remodelling in tendon pathophysiology. Interleukin-33 (IL-33) acting via its receptor ST2 is increasingly recognised as a critical endogenous tissue danger signal that can initiate inflammation. Objectives: We investigated the role of the IL-33/ST2 signallingpathway on tendon pathology in animal and human models of tendinopathy. Results: We show here that human and mouse tendons over express IL-33 when damaged, and drives tenocytes to undergo an early switch in collagen matrix production toward a collagen III phenotype. Moreover, administration of rh IL-33 in an in vivo model of tendinopathy results in reduced biomechanical tendon strength at early time points while neutralising antibodies to IL-33 attenuates these changes. Furthermore we highlight a key regulatory role for the microRNA29 family in IL-33 induced collagen matrix changes through direct targeting of the soluble ST2 receptor and Collagen III. Image/graph: Conclusions: For the first time we provide evidence that IL-33/miR-29 pathway orchestrates inflammatory and matrix responses following tissue injury, and thus may offer future strategies to treat tendon diseases diseases. Disclosure of Interest: None Declared